Pengaruh Inflasi Dan Suku Bunga Terhadap Harga Saham Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Handini Hadistia; Nurlinda Nurlinda (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study was to determine whether there was an effect of inflation and interest rates on stock prices in banking companies listed on the Indonesia Stock Exchange. The object of this research is PT. Bank Negara Indonesia, Tbk. Which share price data was listed on the Indonesia Stock Exchange. The independent variables used in this study were inflation and interest rates, while the dependent variable was stock prices. This study used monthly data from 2017 to 2019 with the data analysis method used in this research was descriptive quantitative, while the analysis model used in this study is multiple linear regression analysis. Testing this hypothesis used the coefficient of determination (R2), partial test (t test) and simultaneous test (F test). The results of this study indicated that simultaneously inflation and interest rates have a positive and significant effect on stock prices, apart from that partially, inflation has no negative and insignificant effect on stock prices, while interest rates have no and insignificant effect on stock prices.